Impact of PCSK9 and acid ceramidase on obese hypothyroidism female patients - Mohammed Rajab Abed AL-Joboury; Nagham Qasim Kadhim; Saif M. Hasan (Peerian Journals Publishing, 2024)
Proprotein Convertase subtilisin Kexin type 9 (PCSK9) is a serine protease composed of 692 residues. Acid ceramidase is an enzyme that hydrolyzed ceramide to sphingosine and fatty acids
Keywords: Hypothyroidism; obesity; PCSK9 and acid ceramidase